Investigation of Thulium and Other Rare Earth Element Mass Fractions in NIST SRM 1632a Bituminous Coal Reference Material by Quadrupole ICP‐MS. Issue 2 (19th February 2018) - Roth, Elliot; Bank, Tracy L.; Granite, Evan
Abstract : Inductively coupled plasma‐mass spectrometry after lithium metaborate fusion and digestion was used to measure the rare earth element (REE) mass fractions of several reference materials including NIST SRM 1632a, a historical bituminous Pennsylvania seam coal. While most of the REE mass fractions measured in this study were consistent with the published consensus data, the measured mass fraction of thulium for NIST SRM 1632a was consistently lower compared with the published data. Chondrite normalisation of the published consensus data for NIST SRM 1632a produced a positive thulium anomaly (Tm = 1.78), which is inconsistent with a terrestrial source of sediment. Normalisation of REE mass fractions collected in this study produced no significant Tm anomaly (Tm = 0.93), which agrees with the sedimentary depositional environment of coal. Therefore, a revised mass fraction of 0.16 mg kg −1 Tm in NIST SRM 1632a is recommended. Abstract : Published consensus data for coal SRM 1632a exhibits a thulium anomaly. New ICP‐MS mass fraction data for coal SRM 1632a shows no thulium anomaly, consistent with expected REE distribution patterns for coal.